Comparative Study of Observation with Theoretical Contrast using the Schaefer and Crumey Methods on the Image Result Observation Using OZT-ALTS Robotic Telescope - Muztaba, Robiatul; Mufidanisa, Yasmin (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2025)
Observing the crescent moon (hilal) is crucial as it significantly impacts religious activities, particularly for the Muslim community. However, there are challenges associated with hilal observation due to its appearance as a young crescent moon, making it very small apparent size, resulting in low visibility. Additionally, hilal observations are conducted before sunset when the sky still retains brightness, causing a narrow contrast between the moon's light and the background sky. This research aims to compare the contrast values obtained from observing the hilal with the OZT-ALTS Robotic Telescope to theoretical hilal values. Two theoretical contrast methods are examined in this study. The observed contrast values show an increase over time, albeit fluctuating due to cloud interference. The Schaefer contrast also increases over time, with values similar to observed contrast. The Crumey contrast decreases approaching dusk but increases after sunset. Spearman correlation analysis is used to investigate the relationship between each contrast. Observation contrast and Schaefer show a positive Spearman correlation of 0.1413. However, the contrast between observation and Crumey shows a negative correlation of -0.0603. The correlation between Schaefer and Crumey also resulted in a negative correlation of -0.8943. Theoretical contrast in this study only shows the ideal model at the time of observation because dynamic environmental factors are difficult to model, thus the relationship between observed and theoretical contrast is weak. The theoretical contrast in this study does not can be used as a reference in hilal observation